Sustainability of One WASH Facilities in the Rural Settings of North Shoa Zone, Amhara Region, North East Ethiopia, 2020 - Muluken Tessama Aemiro; Yohannes Getachew (Journal of Nutrition and Metabolism)
Background. Water, sanitation, and hygiene (WASH) is considered as one term and recognizes that the three are closely related. The Government of Ethiopia launched the programme to improve the way water, and sanitation is provided to the people improving the WASH financing effectively, decreasing school children drop-out rates and improving the health status. The main aim of this study is to assess factors related to the sustainability of one WASH facilities in the rural settings of North Shoa zone, North East Ethipia. Methods. Institutional- and community-based cross-sectional study was conducted. Taking the total number of woredas in the zone, 20 of them were rural project woredas during the first phase of the program and clustered in 6 subzones, and 6 woredas had been selected randomly by the lottery method from each subzones. A total of 768 households were randomly selected based on the proportional size of the number of households in each woreda. A structured questionnaire was used for this study. The data were collected via interview. Multivariable logistic regression analysis was used to identify independent predictors with P<0.05 and confidence interval of 95% considering statistically significant. Result. Among a total of 768 HHs intended to be involved, 689 were involved with 90% response rate. The communities WASH facilities were assessed to be unsustainable by more than half of the respondents (372 (54 percent)) HHs replies. Distance from current water source, community participation during water construction, practice of CLTSH in the village, declaration of open defecation free (ODF) in the village, and existence of health institution near the village were found positively associated with sustainability of one WASH facilities. Conclusion. The sustainability of WASH facilities was revealed to be relatively low. Considering distance from water source, community participation, practice of CLTSH in the village, village declared ODF, and existence of health institution are mandatory to all stake holders participating in WASH activities before, during, and after the implementation of the project.